Efecto de un programa de entrenamiento de fuerza en la potencia máxima de los ciclistas de ruta de la liga del Quindío entre edades de 15 a 18 años. (2015)
This research, which is entitled: effect of a program of strength training at the maximum power of the road cyclist of Quindío´s league with an age range between 15 and 18 years; whose primary objective was to determine the effect of a strength training program at the maximum power in road cyclists of Quindio´s league with an age range between 15-18 years. For which it was taken into account committed theorists in the episteme that concern this research including Platonov, v. (1995); Hawley, j. and Burke, l. (2000); Sarmiento, Garcia, Martin Calderon and Benito (2008). Likewise, it had the active and dedicated work of the participants in this research; that is to say, the subjects of study, in this case the road cyclists of the Quindio´s league. It is worth mentioning that the investigative work belongs to the quantitative methodological approach with an explanatory cross-sectional type of research. For what it was looked during this investigation the greatest objectivity. Accordingly, it reached some consistent results, such us, the acceptance of the research hypothesis where it was stated that it is possible to improve the maximum power of the road cyclist in the Quindio´s league through a training program of general strength, as it analyzes that all the cyclist, who took part in the research, improved their power and their effect was positive according to their initial diagnosis and their final test, in which the athletes were able to reveals a better power state evidenced in the Wingate test that was conducted to them. Also the power expressed in the implementation of the program was not related to the size or weigh of the athletes that participated in the research. Similarly, some conclusions are achieved inherent to the research work carried out. It was concluded that there was a positive effect after running the program, as the highest peak of the athletes ´power were better in the post-test, in addition to achieve it in less time; Regardless of the variables (height, weight, age) of each athlete, it was show an improvement all them in different proportions.